Before and After Avatar Exposure: The Impact of Body Scanning Technology on Body Satisfaction, Mood, and Appearance Management. (April 2018) - Ridgway, Jessica L.
Loker et. al. initiated a call for research investigating how third dimension (3-D) affects one's perceptions of their own body by raising the following questions: Will the ability to see ourselves in 3-D increase body acceptance of normal variations and counteract the popular media images of what constitutes a beautiful body? Or will 3-D views increase dissatisfaction with our real bodies? In response, the researcher guided by self-discrepancy theory, investigated the unique experience of viewing one's body in 3-D on participants' self-reported levels of body satisfaction, mood, and appearance management. Results indicated that viewing one's avatar in 3-D magnifies individuals' actual–ideal (AI) self-discrepancies regardless of gender. The researcher observed decreased body satisfaction and mood when the magnitude of participants' AI discrepancies increased. Both men and women indicated wanting to engage in greater appearance management behaviors postavatar viewing compared to baseline reports. The theoretical and applied implications are discussed.